The Needs Analysis Of English Learning For The Fourth And Fifth Graders - Sihmirmo, Pratelaning (Eduscience : Jurnal Ilmu Pendidikan, 2015)
This is a report of a research aiming at investigating needs of English learning for the fourth and fifth graders of SDN Utan Kayu Utara 01, 03, 05 Pagi Jakarta in Academic Year 2014/2015 in terms of learning materials and ways of learning. To achieve the aim, the researcher distributed questionnaires, conducted interviews, and analyzed various related documents. Questionnaires were distributed by employing incidental convenience purposive sampling to 185 participants. Interviews were conducted to 30 of the participants by employing quota purposive sampling. Documents being investigated were the schools’ vision, mission and goals; the 2013 Curriculum; the English syllabus for SMP students; and the English textbook for the seventh graders. From the investigation, it was revealed that the needs of English learning for the fourth and fifth graders of SDN Utan Kayu Utara 01, 03, 05 Pagi Jakarta in Academic Year 2014/2015 in terms of learning materials are music & songs, animals, arts & literatures, jobs, and family. In terms of ways of learning, the learners’ needs are writing diaries/stories/ teacher’s explanation/ summaries/ sentences/ names of fruits/ names of animals, studying textbooks & exercise books, reading books/ comics/ magazines/ English conversation, listening to music/ teachers/ conversation, making presentation, looking meaning up in a dictionary, working in groups, playing games, using English words in real conversation, and making dialogues. With these findings, the English program designers are suggested to develop an English syllabus which meets the needs of the learners. Keywords: needs, needs analysis, learning materials, ways of learning. Penelitian ini bertujuan menyelidiki kebutuhan pembelajaran bahasa Inggris untuk siswa kelas empat dan kelima dari SDN Utan Kayu Utara 01, 03, 05 Pagi Jakarta di Tahun Akademik 2014/2015 dalam hal bahan dan cara belajar belajar. Untuk mencapai tujuan tersebut, peneliti mendistribusikan kuesioner, melakukan wawancara, dan menganalisis berbagai dokumen terkait. Kuesioner didistribusikan dengan menggunakan kenyamanan insidental purposive sampling untuk 185 peserta. Wawancara dilakukan untuk 30 peserta dengan menggunakan quota sampling purposive. Dokumen yang diteliti adalah sekolah 'visi, misi dan tujuan; 2013 Kurikulum; silabus Bahasa Inggris untuk siswa SMP; dan buku teks bahasa Inggris untuk siswa kelas tujuh. Dari penyelidikan, terungkap bahwa kebutuhan belajar bahasa Inggris untuk siswa kelas empat dan kelima dari SDN Utan Kayu Utara 01, 03, 05 Pagi Jakarta di Tahun Akademik 2014/2015 dalam hal materi pembelajaran adalah musik & lagu, hewan, seni & literatur, pekerjaan, dan keluarga. Dalam hal cara belajar, kebutuhan peserta didik menulis buku harian / cerita / penjelasan / ringkasan / kalimat / nama guru dari buah / nama-nama hewan, mempelajari buku & buku latihan, membaca buku / komik / majalah / percakapan bahasa Inggris, mendengarkan music / guru / percakapan, membuat presentasi, mencari artinya di kamus, bekerja dalam kelompok, bermain game, menggunakan kata-kata bahasa Inggris dalam percakapan nyata, dan membuat dialog. Dengan temuan ini, para desainer Program Bahasa Inggris disarankan untuk mengembangkan silabus bahasa Inggris yang memenuhi kebutuhan peserta didik. Kata Kunci: Kebutuhan, Analisis Kebutuhan, Materi Pembelajaran, Cara Pembelajara